BIOLOGICAL CONTROL OF COTTON DISEASE BY BACTERIAL AGENTS (Scientific journal of the Fergana State University, 2024)
This study investigates the efficacy of eight bacterial strains in controlling root rot of cotton caused by Fusarium oxysporum f in salinated soil conditions. Cotton seedlings are highly susceptible to soil-borne fungal pathogens, leading to significant crop losses despite the use of fungicides. The bacterial isolates were sourced from cotton rhizosphere soils and evaluated for their biocontrol potential. The experiment involved inoculating cotton seeds with bacterial suspensions and growing them in Fusarium-infested salinated soil. Results showed that four bacterial isolates, Pseudomonas chlororaphis TSAU13, Pseudomonas putida TSAU1, Pseudomonas putida 1T1, and Pseudomonas extremorientalis TSAU20, significantly reduced disease incidence by up to 75% compared to the control. These findings highlight the potential of specific bacterial strains as effective biocontrol agents against cotton root rot, offering a sustainable alternative to chemical fungicides. Further research is warranted to explore the genetic diversity of biocontrol microorganisms and their adaptation to specific agricultural environments.